High-strength weather-resistant environment-friendly cement and preparation method thereof

By adding biomass-enhanced composite mineral materials and modified polymer emulsions to the cement formula, combined with specific preparation methods, the problems of high energy consumption, serious pollution and insufficient performance of traditional cement are solved, and cement products with high strength, weather resistance and environmental protection are achieved.

CN119912218APending Publication Date: 2025-05-02西安高新技术产业开发区管理委员会
View PDF 0 Cites 4 Cited by

Patent Information

Application Number
CN202510146952.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-10
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

Traditional cement has problems of high energy consumption and serious pollution during the production process, and it is difficult to maintain good physical and mechanical properties under harsh environmental conditions, which affects the safety and durability of the building.

Method used

High-strength weather-resistant and environmentally friendly cement formulas, including silicate cement, fly ash, slag powder, biomass-enhanced composite mineral materials, nano-silica, modified polymer emulsions and additives, improve the strength and weather resistance of cement through specific preparation methods.

Benefits of technology

It significantly reduces the carbon footprint and resource consumption, improves the compressive strength, toughness and durability of cement, enhances its performance in harsh environments, and promotes the transformation of the construction industry to low-carbon energy-saving.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention belongs to the technical field of cement manufacturing, and particularly relates to high-strength weather-resistant environment-friendly cement and a preparation method thereof. The environment-friendly cement is prepared from the following raw materials in parts by mass: 40 to 55 parts of Portland cement, 15 to 25 parts of fly ash, 10 to 15 parts of slag powder, 6 to 12 parts of biomass reinforced composite mineral material, 2 to 4 parts of nano silicon dioxide, 1 to 4 parts of modified polymer emulsion and 1 to 3 parts of additive. The biomass reinforced composite mineral material is prepared from zeolite, bentonite, sepiolite and chitosan; the modified polymer emulsion comprises a modified polyacrylate emulsion and a modified polystyrene-butadiene emulsion in a mass ratio of (1-3): 1; the additive is prepared from basalt fiber, sodium lignin sulfonate, a rosin thermopolymer and sodium gluconate. The environment-friendly cement prepared by the invention not only has high strength and good weather resistance, but also remarkably reduces carbon footprint and saves natural resources.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of cement manufacturing, and in particular relates to high-strength weather-resistant and environmentally friendly cement and a preparation method thereof. Background Art

[0002] With the rapid development of social economy and the continuous improvement of people's living standards, the construction industry has an increasing demand for building materials. Among them, cement, as one of the most important building materials, plays an irreplaceable role in infrastructure construction, house construction, etc. However, there are problems such as high energy consumption and serious pollution in the traditional cement production process, and its performance during use needs to be improved. Especially in the face of harsh environmental conditions, such as extreme temperature changes, acid and alkali corrosion, etc., traditional cement products are often difficult to maintain good physical and mechanical properties, which not only affects the safety and durability of the building, but also brings great costs to maintenance.

[0003] Specifically, traditional cement has the following problems: Environmental pollution: Cement production is one of the main sources of global carbon dioxide emissions. Every ton of cement produced releases about 0.9 tons of CO2, which poses a serious challenge to global climate change.

[0004] High resource consumption: Traditional cement manufacturing requires a large amount of natural mineral resources such as limestone as raw materials. These resources are non-renewable resources, and long-term mining will lead to resource depletion.

[0005] Insufficient durability: Although ordinary Portland cement has good initial strength, it is prone to cracking or even powdering when exposed to moisture, freeze-thaw cycles or chemical corrosion for a long time, seriously affecting structural safety.

[0006] Limited compressive strength: For some special application scenarios (such as high-rise building foundations, bridge piers, etc.), concrete materials are required to have higher compressive strength and better toughness performance, but existing products are often difficult to fully meet the needs.

[0007] In recent years, in order to overcome the above defects and achieve the goal of green and sustainable development, scientific research institutions at home and abroad have carried out research and development of new environmentally friendly cement. These studies are mainly focused on the following directions: Utilization of industrial waste: By recycling fly ash, slag, steel slag and other industrial solid waste as partial substitutes for raw materials, it reduces environmental pollution and production costs.

[0008] Develop low calorific value cement: Mix different mineral components in specific proportions to reduce the exothermic heat of hydration reaction, thereby reducing the risk of crack formation due to excessive temperature.

[0009] Improve durability: Introduce nanomaterials or modifiers to enhance the internal microstructural stability of the cement matrix, thereby improving the overall waterproof and anti-seepage capabilities and the ability to resist external erosion.

[0010] Improve mechanical properties: Explore the addition of toughening materials such as cellulose and polymer particles to optimize the comprehensive mechanical properties of the composite system, making the finished product more durable.

[0011] Although many research results have been published, there is still a lack of an ideal product on the market that can ensure good environmental protection characteristics while having excellent weather resistance and extraordinary strength. Therefore, how to combine the latest scientific and technological means to develop a new generation of high-performance cement that meets the future development direction has become one of the key issues that need to be solved urgently. Summary of the invention

[0012] The purpose of the present invention is to provide a high-strength weather-resistant and environmentally friendly cement and a preparation method thereof. The cement prepared by the present invention can not only effectively reduce carbon footprint and save natural resources, but also significantly improve the weather resistance and mechanical strength of the material itself, thereby contributing to promoting the transformation of the construction industry in my country and even the world towards low-carbon and energy-saving.

[0013] In order to achieve the above object, the present invention provides the following technical solutions: The first aspect of the present invention provides a high-strength weather-resistant and environmentally friendly cement, comprising the following raw materials in parts by weight: 40 to 55 parts of silicate cement, 15 to 25 parts of fly ash, 10 to 15 parts of slag powder, 6 to 12 parts of biomass-reinforced composite mineral materials, 2 to 4 parts of nano-silicon dioxide, 1 to 4 parts of modified polymer emulsion, and 1 to 3 parts of additives.

[0014] The raw materials for preparing the biomass-enhanced composite mineral material include zeolite, bentonite, sepiolite and chitosan.

[0015] The preparation method of the biomass-enhanced composite mineral material is as follows: (1) zeolite, bentonite and sepiolite are mixed in a mass ratio of 1:(0.5-3):(0.5-3), the mixture is mixed with a 4-10wt% aqueous sulfuric acid solution in a mass ratio of 1:3-5, the mixture is poured into a hydrothermal reactor, and the hydrothermal stirring reaction is carried out for 2-4 hours at a temperature of 150-170°C, a pressure of 1-1.5MPa and a stirring speed of 400-800 r / min; (2) After the hydrothermal reaction is completed, the mixture is filtered, the filter cake is collected, the filter cake is washed until it is neutral, the washed filter cake is dried at 80-100° C. to constant weight, the dried filter cake is calcined at 130-160° C. for 1-3 hours, and then cooled to room temperature to obtain an acid-treated composite mineral material; (3) dissolving chitosan in a 1-5 wt% acetic acid aqueous solution to prepare a chitosan solution with a mass fraction of 1.5-4%, mixing the chitosan solution and water in a mass ratio of 1:4-7, allowing the mixture to swell for 100-140 hours at room temperature, then adding 2-5% sodium dodecyl sulfate by mass of the mixture, stirring for 20-40 minutes, and obtaining a dispersion; (4) Mixing the dispersion with the acid-treated composite mineral material in a mass ratio of 1:0.4-0.6, stirring for 1-3 hours, placing the mixture in a microwave reactor, and treating it for 10-20 minutes at a microwave power of 200-500 W. After the treatment, filtering the mixture, collecting the filter cake, and vacuum drying the filter cake to constant weight to obtain the biomass-enhanced composite mineral material.

[0016] The present invention adds biomass to cement to enhance the composite mineral material, which can significantly improve the strength and weather resistance of cement. Specifically, under high temperature and high pressure conditions, mineral materials such as zeolite, bentonite, and sepiolite are treated with sulfuric acid aqueous solution, undergo physical and chemical changes, and generate composite mineral materials with more stable structures. This process can improve the pore structure of the mineral material and make it more compact. Chitosan has good film-forming properties and biocompatibility. By dissolving chitosan in acetic acid aqueous solution and mixing it with the composite mineral material after acid treatment, and then subjecting it to microwave treatment, chitosan can penetrate into the pore structure of the mineral material. Since chitosan has good hydrophilicity, it can enter the micropores and cracks inside the mineral material. In the subsequent microwave treatment process, chitosan will undergo a certain degree of cross-linking reaction, so that it is fixed in the pore structure inside the mineral material. The cross-linked network structure of chitosan can improve the crack resistance and toughness of the cement matrix, reduce the formation of cracks, and thus improve the overall mechanical properties. The distribution of chitosan in the pores of mineral materials forms a continuous protective layer, which effectively prevents the intrusion of moisture and harmful ions and improves the waterproof and anti-seepage ability of cement. In addition, chitosan will also form a protective film on the surface of mineral materials, which can further enhance the density and toughness of the cement matrix.

[0017] The modified polymer emulsion comprises a modified polyacrylate emulsion and a modified polystyrene-butadiene emulsion in a mass ratio of 1 to 3:1.

[0018] The preparation method of the modified polyacrylate emulsion comprises the following steps: (1) Add the monomer and part of the emulsifier into deionized water and stir evenly to form a pre-emulsion; The monomers are methyl methacrylate (MMA), butyl acrylate (BA), glycidyl methacrylate (GMA) and hydroxyethyl acrylate (HEA), with a mass ratio of 50: (40-45): (2-5): (2-5); the emulsifiers are sodium dodecyl sulfate (SDS) and nonylphenol polyoxyethylene ether (NP-10), with a mass ratio of 1: 1-2; the total mass of the emulsifier is 2-4% of the total mass of the monomers; the emulsifier added in step (1) is 20-30% of the total mass of the emulsifier; (2) Take a clean reactor, add the remaining emulsifier, then add 5-10% of the pre-emulsion, stir evenly, heat to 60-70°C, add part of the initiator solution, react for 20-40 minutes to form a seed emulsion; The initiator solution is a 0.1-0.5 wt% aqueous solution of ammonium persulfate, the mass of the initiator ammonium persulfate is 0.1-0.5% of the total mass of the monomer, and the initiator added in step (2) is 10-20% of the total mass of the initiator; (3) Slowly add the remaining pre-emulsion to the seed emulsion, and at the same time, add the remaining initiator solution. The addition process is controlled within 2 to 3 hours, and the reaction temperature is maintained at 60 to 70 ° C. After the addition is completed, continue to keep the temperature for 1 to 2 hours; (4) dispersing nano-silicon dioxide in deionized water to form a stable suspension, wherein the mass ratio of nano-silicon dioxide to deionized water is 1:(200-500), and the mass of nano-silicon dioxide is 2-5% of the mass of the monomer. The nano-silicon dioxide suspension is pre-treated using an ultrasonic device to ensure that it is fully dispersed and to avoid agglomeration. The nano-silicon dioxide suspension is slowly added to the reaction system of step (3), and the reaction is continued by stirring for 1-2 hours. After the reaction is completed, a sodium bisulfite aqueous solution with a mass concentration of 0.1-0.5% is added to terminate the reaction. The amount of sodium bisulfite added is 0.1-1% of the total mass of the monomer. (5) Cooling the reaction system to room temperature, adjusting the pH value of the emulsion to 7.0-8.0, and obtaining the final modified polyacrylate emulsion.

[0019] The preparation method of the modified polystyrene-butadiene emulsion comprises the following steps: (1) Add the monomer and part of the emulsifier into deionized water and stir evenly to form a pre-emulsion; The monomers are styrene (St), butadiene (Bd), maleic anhydride (MAH), and methyl methacrylate (MMA), with a mass ratio of 50:50-60:2-5:2-5; the emulsifiers are sodium dodecyl sulfate (SDS) and nonylphenol polyoxyethylene ether (NP-10), with a mass ratio of 1:1-2; the total mass of the emulsifier is 2-4% of the total mass of the monomers; the emulsifier added in step (1) is 20-30% of the total mass of the emulsifier; (2) Take a clean reactor, add the remaining emulsifier, then add 5-10% of the pre-emulsion, stir evenly, heat to 70-80°C, add part of the initiator solution, react for 20-40 minutes to form a seed emulsion; The initiator solution is a 0.1-0.5 wt% aqueous solution of ammonium persulfate, the mass of the initiator ammonium persulfate is 0.1-0.5% of the total mass of the monomer, and the initiator added in step (2) is 10-20% of the total mass of the initiator; (3) Slowly add the remaining pre-emulsion to the seed emulsion, and at the same time, add the remaining initiator solution. The addition process is controlled within 2 to 3 hours, and the reaction temperature is maintained at 70 to 80 ° C. After the addition is completed, continue to keep the temperature for 1 to 2 hours; (4) Weigh 0.1-0.5% of the total weight of the monomer N,N'-methylenebisacrylamide (MBAA), dissolve it in deionized water to form a solution with a concentration of 1-5wt%, add the N,N'-methylenebisacrylamide solution to the reaction system of step (3), stir and react for 1-2 hours, after the reaction is completed, add a sodium bisulfite aqueous solution with a mass concentration of 0.1-0.5% to terminate the reaction, the amount of sodium bisulfite added is 0.1-1% of the total weight of the monomer; (5) Cooling the reaction system to room temperature, adjusting the pH value of the emulsion to 7.0-8.0, and obtaining the final modified polystyrene-butadiene emulsion.

[0020] The addition of modified polyacrylate emulsion and modified polystyrene-butadiene emulsion can significantly improve the toughness of cement matrix and reduce the formation of cracks. Modified polymer emulsion can form a continuous polymer film in the cement matrix, enhance the bonding force between the components and improve the overall mechanical properties.

[0021] Functional monomers glycidyl methacrylate and hydroxyethyl acrylate are introduced into the modified polyacrylate emulsion. Glycidyl methacrylate provides epoxy groups, which enhances the bonding force between the emulsion and the inorganic filler, and improves the crosslinking density and chemical resistance of the emulsion; hydroxyethyl acrylate provides hydroxyl groups, which increases the hydrophilicity and reactivity of the emulsion, helps the crosslinking reaction with other components, and improves the comprehensive mechanical properties of the emulsion. The addition of nano-silica can fill the micropores in the emulsion, improve the density and strength of the emulsion, and also improve the wear resistance, corrosion resistance and aging resistance of the emulsion, extending the service life of the material.

[0022] Functional monomers maleic anhydride and methyl methacrylate are introduced into the modified polystyrene-butadiene emulsion. Maleic anhydride provides carboxyl groups, which enhances the polarity and reactivity of the emulsion, improves the bonding force between the emulsion and the inorganic filler, and improves the chemical resistance of the emulsion; methyl methacrylate can further increase the hardness and heat resistance of the emulsion, and balance the rigidity and flexibility of the emulsion. MBAA, as a crosslinking agent, undergoes crosslinking reaction with the monomer during the emulsion polymerization process to form a three-dimensional network structure, which not only improves the crosslinking density and strength of the emulsion, but also enhances the toughness of the emulsion, reduces the generation of cracks, and improves the overall durability and mechanical properties.

[0023] Modified polyacrylate emulsion provides excellent hardness, wear resistance and heat resistance, while modified polystyrene-butadiene emulsion provides good flexibility and impact resistance. The combination of the two can balance the rigidity and flexibility of the cement matrix, improve its comprehensive mechanical properties, and also improve its construction performance, such as fluidity, plasticity and setting time, making construction more convenient and controllable.

[0024] The additive is composed of the following raw materials in parts by mass: 5-10 parts of basalt fiber, 1-2 parts of sodium lignin sulfonate, 2-5 parts of rosin thermal polymer, and 0.5-2 parts of sodium gluconate.

[0025] In the environmentally friendly cement of the present invention, the four additives not only play different functions respectively, but also can produce synergistic effects between other components in the cement. Basalt fiber has high strength and high modulus, can significantly improve the tensile strength and toughness of cement matrix, the fiber forms a three-dimensional network structure in the cement matrix, effectively disperses stress, reduces the generation and expansion of cracks, and the presence of fiber improves the overall stability and durability of the cement matrix, especially in harsh environments such as freeze-thaw cycles and salt spray corrosion. Rosin thermopolymer can reduce the viscosity of cement slurry, improve its plasticity and fluidity, and make cement easier to stir and pour. Sodium lignin sulfonate and sodium gluconate act as retarders, and their combined action can significantly prolong the setting time of cement, so that there is more time for adjustment and operation during the construction process. Sodium lignin sulfonate and rosin thermopolymer indirectly enhance the mechanical properties of cement matrix by improving the density and uniformity of cement slurry, and these two additives also make the distribution of basalt fiber in cement matrix more uniform, thereby improving the overall strength and toughness. The film layer formed by the rosin thermopolymer combined with the filling effect of nano-silicon dioxide improves the waterproof and anti-seepage ability of the cement matrix. The three-dimensional network structure formed by basalt fiber in the cement matrix, combined with the dense microstructure of the biomass-reinforced composite mineral material, further enhances the microstructural stability of the cement matrix.

[0026] The second aspect of the present invention provides a method for preparing the above-mentioned high-strength weather-resistant and environmentally friendly cement, comprising the following steps: (1) Weigh the raw materials according to the formula, and use a dry mixer or a blender to evenly mix the dry materials such as silicate cement, fly ash, slag powder, biomass reinforced composite mineral material, nano-silicon dioxide, basalt fiber, sodium lignin sulfonate, rosin thermal polymer, sodium gluconate, etc.; (2) spraying the modified polymer emulsion onto the powder mixed in step (1) through a spray drying device, wherein the inlet air temperature of the spray drying device is 180-220°C and the outlet air temperature is 90-110°C; (3) After spray drying, use a dry mixer or a stirrer to mix again to ensure that the modified polymer emulsion is evenly distributed in the dry powder to obtain high-strength weather-resistant and environmentally friendly cement.

[0027] Compared with the prior art, the advantages and beneficial effects of the present invention are: The present invention provides a high-strength weather-resistant and environmentally friendly cement, which significantly improves the comprehensive performance of cement through a specific raw material ratio and preparation method. The biomass-reinforced composite mineral material enhances the microstructural stability of cement through its special preparation method, and further improves its ability to resist freeze-thaw cycles and chemical corrosion. The addition of modified polyacrylate emulsion and modified polystyrene-butadiene emulsion improves the toughness and crack resistance of the cement matrix and reduces the formation of cracks. The combined use of additives enhances the tensile strength and toughness of cement, improves plasticity and fluidity, is conducive to forming a stable three-dimensional network structure, and improves overall stability and durability. Nano-silicon dioxide fills micropores to improve density and waterproof and anti-seepage capabilities. In addition, the use of industrial waste such as fly ash and slag powder not only saves resources but also reduces environmental pollution, so that the cement has good environmental protection characteristics while maintaining excellent performance. DETAILED DESCRIPTION

[0028] The technical scheme in the embodiment of the present invention will be clearly and completely described below. Obviously, the described embodiment is only a part of the embodiment of the present invention, rather than all the embodiments. Based on the embodiment in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. In addition, it is worth noting that the raw materials involved in the present invention are all common commercial products unless otherwise specified.

[0029] The following sources of raw materials are provided for illustrative purposes: Zeolite was purchased from Hebei Jinglong New Materials Co., Ltd., with an average mesh size of 200; Bentonite was purchased from Shandong Huayuan Mining Co., Ltd., with an average mesh size of 200; Sepiolite was purchased from Sichuan Xinda Sepiolite Technology Co., Ltd., with a length of 10-20 μm and a diameter of 1-5 μm; Chitosan was purchased from Zhejiang Jinke Biochemical Co., Ltd., with an average mesh size of 200; Portland cement was purchased from China National Building Materials Group, P·O 42.5R ordinary Portland cement; Fly ash was purchased from Shanxi Coking Coal Group, with a fineness of ≤12%; Slag powder was purchased from Baosteel Resources Co., Ltd., S95 grade slag powder, specific surface area ≥ 400 m² / kg; Nano-silicon dioxide was purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd., with a particle size of 30-50 nm; Basalt fiber was purchased from Sichuan Aerospace Tuoxin Basalt Industry Co., Ltd., with a single fiber diameter of 9-13 μm; Sodium lignin sulfonate was purchased from Jiangsu Ruibang Agrochemical Co., Ltd., with an average mesh size of 200; Rosin thermal polymer was purchased from Guangxi Wuzhou Rosin Co., Ltd.; Sodium gluconate was purchased from Henan Xintiandi Chemical Co., Ltd., with an average mesh size of 200.

[0030] Example 1 This embodiment provides a method for preparing a biomass-reinforced composite mineral material, comprising the following steps: (1) Zeolite, bentonite and sepiolite were mixed in a mass ratio of 1:1:2, the mixture was mixed with a 5wt% aqueous sulfuric acid solution in a mass ratio of 1:4, the mixture was poured into a hydrothermal reactor, and the hydrothermal stirring reaction was carried out for 3 hours at a temperature of 160°C, a pressure of 1.5MPa and a stirring speed of 600 r / min; (2) After the hydrothermal reaction is completed, the mixture is filtered, the filter cake is collected, the filter cake is washed until it is neutral, the washed filter cake is dried at 90° C. to constant weight, the dried filter cake is calcined at 140° C. for 2 hours, and then cooled to room temperature to obtain an acid-treated composite mineral material; (3) Dissolving chitosan in a 3 wt % acetic acid aqueous solution to prepare a 2 wt % chitosan solution, mixing the chitosan solution and water in a mass ratio of 1:6, allowing the mixture to swell for 120 hours at room temperature, then adding 4 wt % sodium dodecyl sulfate to the mixture, stirring for 30 minutes, and obtaining a dispersion; (4) The dispersion was mixed with the acid-treated composite mineral material in a mass ratio of 1:0.5, stirred for 2 hours, and the mixture was placed in a microwave reactor and treated for 15 minutes at a microwave power of 300 W. After the treatment, the mixture was filtered and the filter cake was collected. The filter cake was vacuum dried to constant weight to obtain the biomass-enhanced composite mineral material, which was a light gray powder.

[0031] Example 2 This embodiment provides a method for preparing a modified polyacrylate emulsion, comprising the following steps: (1) Add the monomer and part of the emulsifier into deionized water and stir evenly to form a pre-emulsion; The monomers are methyl methacrylate, butyl acrylate, glycidyl methacrylate and hydroxyethyl acrylate in a mass ratio of 50:41:3:3; the emulsifiers are sodium dodecyl sulfate and nonylphenol polyoxyethylene ether in a mass ratio of 1:1; the total mass of the emulsifier is 3% of the total mass of the monomers and the emulsifier added in step (1) is 24% of the total mass of the emulsifier; (2) Take a clean reactor, add the remaining emulsifier, then add 8% of the total mass of the pre-emulsion, stir evenly, heat to 65°C, add part of the initiator solution, react for 30 minutes to form a seed emulsion; The initiator solution is a 0.3 wt% ammonium persulfate aqueous solution, the mass of the initiator ammonium persulfate is 0.3% of the total mass of the monomers, and the initiator added in step (2) is 12% of the total mass of the initiator; (3) Slowly add the remaining pre-emulsion solution to the seed emulsion, and at the same time, add the remaining initiator solution. The addition process is controlled to be about 2 hours, and the reaction temperature is maintained at 65°C. After the addition is completed, continue to keep the temperature for 2 hours; (4) dispersing nano-silicon dioxide in deionized water to form a stable suspension, wherein the mass ratio of nano-silicon dioxide to deionized water is 1:300, and the mass of nano-silicon dioxide is 3% of the mass of the monomer. The nano-silicon dioxide suspension is pre-treated using an ultrasonic device to ensure that it is fully dispersed and to avoid agglomeration. The nano-silicon dioxide suspension is slowly added to the reaction system of step (3), and the reaction is continued with stirring for 1.5 hours. After the reaction is completed, a sodium bisulfite aqueous solution with a mass concentration of 0.3% is added to terminate the reaction, and the amount of sodium bisulfite added is 0.4% of the total mass of the monomer; (5) Cooling the reaction system to room temperature, adjusting the pH value of the emulsion to 7.5, and obtaining the final modified polyacrylate emulsion.

[0032] Example 3 This embodiment provides a method for preparing a modified polystyrene-butadiene emulsion, comprising the following steps: (1) Add the monomer and part of the emulsifier into deionized water and stir evenly to form a pre-emulsion; The monomers are styrene, butadiene, maleic anhydride and methyl methacrylate in a mass ratio of 50:55:3:3; the emulsifiers are sodium dodecyl sulfate and nonylphenol polyoxyethylene ether in a mass ratio of 1:1.5; the total mass of the emulsifier is 3% of the total mass of the monomers and the emulsifier added in step (1) is 25% of the total mass of the emulsifier; (2) Take a clean reactor, add the remaining emulsifier, then add 8% of the pre-emulsion, stir evenly, heat to 75°C, add part of the initiator solution, react for 30 minutes to form a seed emulsion; The initiator solution is a 0.3 wt% ammonium persulfate aqueous solution, the mass of the initiator ammonium persulfate is 0.4% of the total mass of the monomers, and the initiator added in step (2) is 16% of the total mass of the initiator; (3) Slowly add the remaining pre-emulsion to the seed emulsion, and at the same time, add the remaining initiator solution. The addition process is controlled within 2.5 hours, and the reaction temperature is maintained at 75°C. After the addition is completed, continue to keep the temperature for 1.5 hours; (4) Weigh 0.2% of the total weight of the monomer N,N'-methylenebisacrylamide and dissolve it in deionized water to form a solution with a concentration of 2wt%. Add the N,N'-methylenebisacrylamide solution to the reaction system of step (3) and stir to react for 2 hours. After the reaction is completed, add a 0.3% sodium bisulfite aqueous solution to terminate the reaction. The amount of sodium bisulfite added is 0.4% of the total weight of the monomer. (5) After the reaction is completed, the reaction system is cooled to room temperature, and the pH value of the emulsion is adjusted to 7.0 to obtain the final modified polystyrene-butadiene emulsion.

[0033] Example 4 The present embodiment provides a high-strength weather-resistant and environmentally friendly cement, comprising the following raw materials in parts by weight: 50 parts of silicate cement, 20 parts of fly ash, 12 parts of slag powder, 10 parts of biomass-reinforced composite mineral material, 3 parts of nano-silicon dioxide, 3 parts of modified polymer emulsion, and 2 parts of additives.

[0034] The biomass-reinforced composite mineral material is prepared by the method of Example 1, the modified polymer emulsion is a modified polyacrylate emulsion and a modified polystyrene-butadiene emulsion in a mass ratio of 2:1, which are prepared by the methods of Examples 2 and 3 respectively, and the additive consists of the following raw materials in parts by mass: 8 parts of basalt fiber, 1.5 parts of sodium lignin sulfonate, 3 parts of rosin thermal polymer, and 1.5 parts of sodium gluconate.

[0035] The preparation method of the high-strength weather-resistant and environmentally friendly cement comprises the following steps: (1) Weigh the raw materials according to the formula, and use a dry mixer to evenly mix the dry materials such as silicate cement, fly ash, slag powder, biomass reinforced composite mineral material, nano silicon dioxide, basalt fiber, sodium lignin sulfonate, rosin thermal polymer, sodium gluconate, etc.; (2) spraying the modified polymer emulsion onto the dry-mixed powder in step (1) through a spray drying device, wherein the inlet air temperature of the spray drying device is 200° C. and the outlet air temperature is 100° C.; (3) After spray drying, the mixture is mixed again using a dry mixer to ensure that the modified polymer emulsion is evenly distributed in the dry powder to obtain high-strength weather-resistant and environmentally friendly cement.

[0036] Example 5 The present embodiment provides a high-strength weather-resistant and environmentally friendly cement, comprising the following raw materials in parts by weight: 50 parts of silicate cement, 25 parts of fly ash, 10 parts of slag powder, 6 parts of biomass-reinforced composite mineral material, 3 parts of nano-silicon dioxide, 4 parts of modified polymer emulsion, and 2 parts of additives.

[0037] The additive is composed of the following raw materials in parts by mass: 6 parts of basalt fiber, 2 parts of sodium lignin sulfonate, 3 parts of rosin thermal polymer, and 2 parts of sodium gluconate.

[0038] The rest is the same as Example 4.

[0039] Comparative Example 1 The difference between this comparative example and Example 4 is that the biomass reinforced composite mineral material is replaced with silica fume.

[0040] Comparative Example 2 The difference between this comparative example and Example 4 is that the preparation method of the biomass-enhanced composite mineral material is as follows: (1) Silica fume, perlite and kaolin were mixed in a mass ratio of 1:1:2, the mixture was mixed with a 5wt% sulfuric acid aqueous solution in a mass ratio of 1:4, the mixture was poured into a hydrothermal reactor, and the hydrothermal stirring reaction was carried out for 3 hours at a temperature of 160°C, a pressure of 1.5MPa and a stirring speed of 600 r / min; (2) After the hydrothermal reaction is completed, the mixture is filtered, the filter cake is collected, the filter cake is washed until it is neutral, the washed filter cake is dried at 90° C. to constant weight, the dried filter cake is calcined at 140° C. for 2 hours, and then cooled to room temperature to obtain an acid-treated composite mineral material; (3) Dissolving chitosan in a 3 wt % acetic acid aqueous solution to prepare a 2 wt % chitosan solution, mixing the chitosan solution and water in a mass ratio of 1:6, allowing the mixture to swell for 120 hours at room temperature, then adding 4 wt % sodium dodecyl sulfate to the mixture, stirring for 30 minutes, and obtaining a dispersion; (4) The dispersion was mixed with the acid-treated composite mineral material in a mass ratio of 1:0.5, stirred for 2 hours, and the mixture was frozen at -20°C. After the mixture solidified, it was thawed at room temperature. This freeze-thaw cycle was repeated 3 times. After the last thawing, the mixture was filtered, the filter cake was collected, and the filter cake was vacuum dried to constant weight to obtain the biomass-enhanced composite mineral material.

[0041] Comparative Example 3 The difference between this comparative example and Example 4 is that the modified polymer emulsion is replaced by common commercially available polyacrylate emulsion and polystyrene-butadiene emulsion, and the mass ratio of the two is 2:1.

[0042] Comparative Example 4 The difference between this comparative example and Example 4 is that the modified polymer emulsion only uses modified polyacrylate emulsion.

[0043] Comparative Example 5 The difference between this comparative example and Example 4 is that the additive is composed of the following raw materials in parts by mass: 3 parts of basalt fiber, 2 parts of sodium lignin sulfonate, 3 parts of rosin thermal polymer, and 3 parts of sodium gluconate.

[0044] Comparative Example 6 The difference between this comparative example and Example 4 is that the additive consists of the following raw materials in parts by mass: 8 parts of glass fiber, 1.5 parts of sodium lignin sulfonate, 3 parts of rosin thermal polymer, and 1.5 parts of sodium gluconate.

[0045] Comparative Example 7 The difference between this comparative example and Example 4 is that the formula of the environmentally friendly cement is as follows: 60 parts of silicate cement, 25 parts of fly ash, 4 parts of slag powder, 5 parts of biomass reinforced composite mineral material, 1 part of nano silicon dioxide, 3 parts of modified polymer emulsion, and 2 parts of additives.

[0046] Performance test 1 Strength test The compressive strength and flexural strength of the environmentally friendly cement prepared in Examples 4-5 and Comparative Examples 1-7 were tested according to the method in GB / T17671-1999 "Cement Mortar Strength Test". The test results are shown in Table 1.

[0047] Table 1 Compressive strength and flexural strength test results

[0048] The above results show that the environmentally friendly cement prepared by the present invention exhibits higher compressive strength and flexural strength. In Comparative Example 1, the biomass-reinforced composite mineral material is replaced with silica fume. Although silica fume can improve the early strength of cement, its long-term durability and toughness are not as good as those of biomass-reinforced composite mineral materials. The preparation method of the biomass-reinforced composite mineral material in Comparative Example 2 is different, and the raw materials and processing conditions used do not achieve the best results, which affects the performance of the final product. In Comparative Example 3, the ordinary commercially available emulsion lacks modification treatment and cannot provide the same toughening effect, resulting in performance degradation. Comparative Example 4 only uses modified polyacrylate emulsion, lacks the synergistic effect of modified polystyrene-butadiene emulsion, and a single emulsion cannot provide sufficient toughening effect, affecting the overall performance. The changes in the proportion and type of additives in Comparative Examples 5 and 6 affect the mechanical properties of cement, resulting in performance degradation. The formula ratio of Comparative Example 7 is different, which affects the mechanical properties of cement and leads to performance degradation.

[0049] Performance Test 2 Weathering Test The environmentally friendly cement prepared in Examples 4-5 and Comparative Examples 1-7 was subjected to freeze-thaw cycle test and salt spray corrosion test to evaluate the weather resistance of the cement. The test method is as follows: Freeze-thaw cycle test: Prepare a specimen of standard size (100mm×100mm×400mm). After 28 days of standard curing, soak the specimen in water to fully absorb water to saturation. Place the specimen in a freezer and freeze it at -18°C for 24 hours. Take out the specimen and thaw it at room temperature for 24 hours. Repeat the above freeze-thaw cycle for 300 cycles. After each 100 cycles, measure the mass loss and compressive strength change of the specimen. The test results are shown in Table 2: Table 2 Freeze-thaw cycle test results

[0050] Salt spray corrosion test: Prepare a standard size specimen (100mm×100mm×400mm), place the specimen in a salt spray test chamber after 28 days of standard curing. Spray a 5% NaCl solution, keep the temperature at 35°C and the humidity at 95%, spray continuously for 24 hours, stop spraying, and let the specimen dry naturally in the test chamber for 24 hours. Repeat the above spray and drying cycle for 7 days. Measure the mass loss and compressive strength change of the specimen after 3 days and 7 days of cycling:

[0051] The above results show that the environmentally friendly cement prepared by the present invention has excellent weather resistance. The present invention uses biomass-reinforced composite mineral materials in the cement formula. This material enhances the microstructural stability of the cement through a special preparation method and improves its ability to resist freeze-thaw cycles and chemical corrosion; the use of modified polymer emulsion improves the toughness of the cement and reduces the formation of cracks; the additives further enhance the mechanical properties and durability of the cement.

[0052] The silica fume used in Comparative Example 1 lacks the organic components in the biomass-enhanced composite mineral material, which helps to form a more uniform and dense microstructure, thereby improving the durability and corrosion resistance of cement; silica fume is prone to more microcracks in freeze-thaw cycles and salt spray corrosion, resulting in a large mass loss and a significant decrease in compressive strength. Comparative Example 2 uses different raw materials and preparation methods to prepare biomass-enhanced composite mineral materials, and this preparation method cannot form the same microstructural stability as in Example 4. The ordinary commercially available emulsion in Comparative Example 3 is prone to cracking during freeze-thaw cycles and cannot effectively prevent the intrusion of moisture and harmful ions; in the salt spray corrosion test, the ordinary emulsion cannot provide a sufficient protective layer, making the cement matrix more susceptible to erosion. In Comparative Example 4, the single emulsion cannot form a complete protective layer, causing the cement matrix to be more susceptible to microcracks in freeze-thaw cycles; in the salt spray corrosion test, the single emulsion is also difficult to provide sufficient protection, making the cement matrix more susceptible to corrosion. In Comparative Example 5, the basalt fiber content is low and cannot provide sufficient reinforcement effect. The proportion of sodium lignin sulfonate and sodium gluconate is high, which makes the cement matrix too soft and reduces its ability to resist freeze-thaw cycles and chemical corrosion. The mechanical properties and durability of the glass fiber in Comparative Example 6 are not as good as those of basalt fibers. Especially in freeze-thaw cycles, the glass fiber is more likely to break. In addition, the interfacial bonding between the glass fiber and the cement matrix is ​​weak, which makes the cement matrix more prone to cracks and peeling in freeze-thaw cycles and salt spray corrosion tests. The increase of silicate cement and fly ash in Comparative Example 7 may increase the porosity of the cement matrix and reduce its density; the reduction of biomass-reinforced composite mineral materials and nano-silica weakens the microstructural stability of the cement matrix, making it more vulnerable to damage in freeze-thaw cycles and salt spray corrosion tests.

[0053] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A high-strength weather-resistant and environmentally friendly cement, characterized in that: The invention comprises the following raw materials in parts by weight: 40-55 parts of silicate cement, 15-25 parts of fly ash, 10-15 parts of slag powder, 6-12 parts of biomass-enhanced composite mineral material, 2-4 parts of nano silicon dioxide, 1-4 parts of modified polymer emulsion, and 1-3 parts of additives; The raw materials for preparing the biomass-enhanced composite mineral material include zeolite, bentonite, sepiolite and chitosan; The modified polymer emulsion includes a modified polyacrylate emulsion and a modified polystyrene-butadiene emulsion in a mass ratio of 1 to 3:1; The additive is composed of the following raw materials in parts by mass: 5-10 parts of basalt fiber, 1-2 parts of sodium lignin sulfonate, 2-5 parts of rosin thermal polymer, and 0.5-2 parts of sodium gluconate.

2. The high-strength weather-resistant and environmentally friendly cement according to claim 1 is characterized in that: The preparation method of the biomass-enhanced composite mineral material is as follows: (1) zeolite, bentonite and sepiolite are mixed in a mass ratio of 1:(0.5-3):(0.5-3), the mixture is mixed with a 4-10wt% aqueous solution of sulfuric acid in a mass ratio of 1:3-5, the mixture is poured into a hydrothermal reactor, and a hydrothermal stirring reaction is carried out for 2-4 hours; (2) After the hydrothermal reaction is completed, the mixture is filtered, the filter cake is collected, the filter cake is washed until it is neutral, the washed filter cake is dried to a constant weight, the dried filter cake is calcined at 130-160° C. for 1-3 hours, and then cooled to room temperature to obtain an acid-treated composite mineral material; (3) dissolving chitosan in a 1-5 wt% acetic acid aqueous solution to prepare a chitosan solution with a mass fraction of 1.5-4%, mixing the chitosan solution and water in a mass ratio of 1:4-7, allowing the mixture to swell for 100-140 hours at room temperature, then adding 2-5% sodium dodecyl sulfate by mass of the mixture, stirring for 20-40 minutes, and obtaining a dispersion; (4) Mixing the dispersion with the acid-treated composite mineral material in a mass ratio of 1:0.4-0.6, stirring for 1-3 hours, placing the mixture in a microwave reactor, and treating it for 10-20 minutes at a microwave power of 200-500 W. After the treatment, filtering the mixture, collecting the filter cake, and vacuum drying the filter cake to constant weight to obtain the biomass-enhanced composite mineral material.

3. The high-strength weather-resistant and environmentally friendly cement according to claim 2 is characterized in that: The hydrothermal stirring reaction in step (1) is carried out at a temperature of 150-170°C, a pressure of 1-1.5 MPa, and a stirring speed of 400-800 r / min; the filter cake drying temperature in step (2) is 80-100°C.

4. The high-strength weather-resistant and environmentally friendly cement according to claim 1 is characterized in that: The preparation method of the modified polyacrylate emulsion comprises the following steps: (1) Adding monomers and part of the emulsifier into deionized water and stirring evenly to form a pre-emulsion, wherein the monomers are methyl methacrylate, butyl acrylate, glycidyl methacrylate and hydroxyethyl acrylate; and the emulsifiers are sodium dodecyl sulfate and nonylphenol polyoxyethylene ether; (2) Take a clean reactor, add the remaining emulsifier, then add 5-10% of the pre-emulsion, stir evenly, heat to 60-70°C, add part of the initiator solution, the initiator solution is an aqueous solution of ammonium persulfate, react for 20-40 minutes to form a seed emulsion; (3) Slowly add the remaining pre-emulsion to the seed emulsion, and at the same time, add the remaining initiator solution. The addition process is controlled within 2 to 3 hours, and the reaction temperature is maintained at 60 to 70 ° C. After the addition is completed, continue to keep the temperature for 1 to 2 hours; (4) dispersing nano-silicon dioxide in deionized water to form a stable suspension, wherein the mass ratio of nano-silicon dioxide to deionized water is 1:(200-500), and the mass of nano-silicon dioxide is 2-5% of the mass of the monomer. The nano-silicon dioxide suspension is pre-treated using an ultrasonic device to ensure that it is fully dispersed and to avoid agglomeration. The nano-silicon dioxide suspension is slowly added to the reaction system of step (3), and the reaction is continued by stirring for 1-2 hours. After the reaction is completed, a sodium bisulfite aqueous solution with a mass concentration of 0.1-0.5% is added to terminate the reaction. The amount of sodium bisulfite added is 0.1-1% of the total mass of the monomer. (5) Cooling the reaction system to room temperature, adjusting the pH value of the emulsion to 7.0-8.0, and obtaining the final modified polyacrylate emulsion.

5. The high-strength weather-resistant and environmentally friendly cement according to claim 4 is characterized in that: The mass ratio of methyl methacrylate, butyl acrylate, glycidyl methacrylate and hydroxyethyl acrylate is 50:(40-45):(2-5):(2-5), the mass ratio of sodium dodecyl sulfate and nonylphenol polyoxyethylene ether is 1:1-2, the total mass of the emulsifier is 2-4% of the total mass of the monomers, and the emulsifier added in step (1) is 20-30% of the total mass of the emulsifier.

6. The high-strength weather-resistant and environmentally friendly cement according to claim 4 is characterized in that: The concentration of the ammonium persulfate aqueous solution is 0.1-0.5 wt %, the mass of the initiator ammonium persulfate is 0.1-0.5 wt % of the total mass of the monomers, and the initiator added in step (2) is 10-20 % of the total mass of the initiator.

7. The high-strength weather-resistant and environmentally friendly cement according to claim 1 is characterized in that: The preparation method of the modified polystyrene-butadiene emulsion comprises the following steps: (1) Adding monomers and part of the emulsifier into deionized water and stirring evenly to form a pre-emulsion, the monomers are styrene, butadiene, maleic anhydride, and methyl methacrylate, and the emulsifiers are sodium dodecyl sulfate and nonylphenol polyoxyethylene ether; (2) Take a clean reactor, add the remaining emulsifier, then add 5-10% of the pre-emulsion, stir evenly, heat to 70-80°C, add part of the initiator solution, the initiator solution is an aqueous solution of ammonium persulfate, react for 20-40 minutes to form a seed emulsion; (3) Slowly add the remaining pre-emulsion to the seed emulsion, and at the same time, add the remaining initiator solution. The addition process is controlled within 2 to 3 hours, and the reaction temperature is maintained at 70 to 80 ° C. After the addition is completed, continue to keep the temperature for 1 to 2 hours; (4) Weigh 0.1-0.5% of the total weight of the monomer N,N'-methylenebisacrylamide (MBAA), dissolve it in deionized water to form a solution with a concentration of 1-5wt%, add the N,N'-methylenebisacrylamide solution to the reaction system of step (3), stir and react for 1-2 hours, after the reaction is completed, add a sodium bisulfite aqueous solution with a mass concentration of 0.1-0.5% to terminate the reaction, the amount of sodium bisulfite added is 0.1-1% of the total weight of the monomer; (5) Cooling the reaction system to room temperature, adjusting the pH value of the emulsion to 7.0-8.0, and obtaining the final modified polystyrene-butadiene emulsion.

8. The high-strength weather-resistant and environmentally friendly cement according to claim 7, characterized in that: The mass ratio of styrene, butadiene, maleic anhydride and methyl methacrylate is 50:50-60:2-5:2-5; the mass ratio of sodium dodecyl sulfate and nonylphenol polyoxyethylene ether is 1:1-2; the total mass of the emulsifier is 2-4% of the total mass of the monomers; and the emulsifier added in step (1) is 20-30% of the total mass of the emulsifier.

9. The high-strength weather-resistant and environmentally friendly cement according to claim 7, characterized in that: The concentration of the ammonium persulfate aqueous solution is 0.1-0.5 wt %, the mass of the initiator ammonium persulfate is 0.1-0.5 wt % of the total mass of the monomers, and the initiator added in step (2) is 10-20 % of the total mass of the initiator.

10. The method for preparing the high-strength weather-resistant and environmentally friendly cement according to any one of claims 1 to 9 comprises the following steps: (1) Weigh the raw materials according to the formula, and use a dry mixer or a blender to evenly mix the dry materials such as silicate cement, fly ash, slag powder, biomass reinforced composite mineral material, nano-silicon dioxide, basalt fiber, sodium lignin sulfonate, rosin thermal polymer, sodium gluconate, etc.; (2) spraying the modified polymer emulsion onto the powder mixed in step (1) through a spray drying device, wherein the inlet air temperature of the spray drying device is 180-220°C and the outlet air temperature is 90-110°C; (3) After spray drying, use a dry mixer or a stirrer to mix again to ensure that the modified polymer emulsion is evenly distributed in the dry powder to obtain high-strength weather-resistant and environmentally friendly cement.

Citation Information

Cited By

  • Freeze-thaw resistant high-strength brick and preparation method thereof

    CN120647295A

  • A freeze-thaw resistant high-strength brick and a method for preparing the same

    CN120647295B

  • Inorganic composite high-strength oil-water well water shutoff material and preparation method thereof

    CN121379548A

  • Ecological corrosion-resistant cement and preparation method thereof

    CN121913716A